2014
DOI: 10.1002/2014jc009963
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating SMOS sea ice thickness into a coupled ice‐ocean model using a local SEIK filter

Abstract: The impact of assimilating sea ice thickness data derived from ESA's Soil Moisture and Ocean Salinity (SMOS) satellite together with Special Sensor Microwave Imager/Sounder (SSMIS) sea ice concentration data of the National Snow and Ice Data Center (NSIDC) in a coupled sea ice-ocean model is examined. A period of 3 months from 1 November 2011 to 31 January 2012 is selected to assess the forecast skill of the assimilation system. The 24 h forecasts and longer forecasts are based on the Massachusetts Institute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 43 publications
(87 reference statements)
2
82
0
Order By: Relevance
“…These studies follow from the first attempt of assimilation of SMOS-Ice with the LSEIK in a regional MITgcm configuration (Yang et al, 2014). Compared to this study, it is found that assimilation of SMOS-Ice has a more moderate impact.…”
Section: Summary and Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…These studies follow from the first attempt of assimilation of SMOS-Ice with the LSEIK in a regional MITgcm configuration (Yang et al, 2014). Compared to this study, it is found that assimilation of SMOS-Ice has a more moderate impact.…”
Section: Summary and Discussionmentioning
confidence: 44%
“…This may be related to the fact that TOPAZ uses a more complete observation network and that the assimilation has been spun up over a longer period of time (from 1989). We also find that assimilation of SMOS-Ice is comparatively larger in October-November than in February-March the time period when Yang et al (2014) tested assimilation of SMOS-Ice. We also verified that assimilation of SMOS-Ice does not degrade ocean variables (SST and SLA), which could happen with a strongly coupled data assimilation scheme.…”
Section: Summary and Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This assessment is a first necessary step towards the eventual assimilation of these observational data, because large systematic errors in either the observations or the forecast model will make successful data assimilation difficult. Previous studies report slightly positive results overall when assimilating L-band sea-ice thickness observations (Yang et al, 2014;Xie et al, 2016) but without doubting the validity of the observational data. As we will show here, both reanalysis and observations can contain large and systematic errors.…”
Section: Introductionmentioning
confidence: 89%